2021
DOI: 10.1089/heq.2020.0037
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Area Deprivation Index and Patient-Reported Outcomes in Patients with Advanced Cancer

Abstract: Background: This analysis describes associations between area deprivation and patient-reported outcomes among patients with advanced cancer. Methods: This is a cross-sectional analysis of baseline data from a multisite primary palliative care intervention trial. Participants were adult patients with advanced cancer. Patient-level area deprivation scores were calculated using the Area Deprivation Index (ADI). Quality of life and symptom burden were measured. Uni-and multivariate regressions estimated associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 55 publications
6
34
0
Order By: Relevance
“…Neighborhood disadvantage has been reported to be associated with (1) increased cancer prevalence, incidence, and mortality 8 , 46 ; (2) obesity and inferior overall survival among pediatric patients with acute lymphoblastic leukemia 61 , 62 ; (3) lack of adjuvant therapy among patients with localized pancreatic cancer 63 ; and (4) anxiety among patients with advanced cancer. 64 One SEER study 8 reported higher ADI (neighborhood disadvantage) to be associated with worse overall survival among cancer patients diagnosed between 1988 and 1999: HRs (highest decile vs lowest decile) were 1.68 (95% CI, 1.57-1.79) for breast, 1.57 (95% CI, 1.46-1.68) for prostate, 1.29 (95% CI, 1.23-1.36) for colorectal, and 1.56 (95% CI, 1.54-1.59) for all cancers. However, such survival estimates were not adjusted for cancer stage and treatment and may not accurately reflect the associations of neighborhood disadvantage with cancer survival, given that stage and treatment are key factors influencing the prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Neighborhood disadvantage has been reported to be associated with (1) increased cancer prevalence, incidence, and mortality 8 , 46 ; (2) obesity and inferior overall survival among pediatric patients with acute lymphoblastic leukemia 61 , 62 ; (3) lack of adjuvant therapy among patients with localized pancreatic cancer 63 ; and (4) anxiety among patients with advanced cancer. 64 One SEER study 8 reported higher ADI (neighborhood disadvantage) to be associated with worse overall survival among cancer patients diagnosed between 1988 and 1999: HRs (highest decile vs lowest decile) were 1.68 (95% CI, 1.57-1.79) for breast, 1.57 (95% CI, 1.46-1.68) for prostate, 1.29 (95% CI, 1.23-1.36) for colorectal, and 1.56 (95% CI, 1.54-1.59) for all cancers. However, such survival estimates were not adjusted for cancer stage and treatment and may not accurately reflect the associations of neighborhood disadvantage with cancer survival, given that stage and treatment are key factors influencing the prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…Neighborhood disadvantage has been reported to be associated with (1) increased cancer prevalence, incidence, and mortality 8,46 ; (2) obesity and inferior overall survival among pediatric patients with acute lymphoblastic leukemia 61,62 ; (3) lack of adjuvant therapy among patients with localized pancreatic cancer 63 ; and (4) anxiety among patients with advanced cancer. 64 One SEER study 8 95% CI, 1.13-1.28), and cancer-specific survival (HR, 1.27; 95% CI, 1.18-1.37), suggesting that even in this group of trial participants who initially all had access to high-quality cancer care, there were still survival disparities across strata of neighborhood SES. Given that all cancer types were combined and separate analyses were not conducted, it was unclear which cancers were primarily subject to neighborhood socioeconomic disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low back pain (cLBP) refers to a persistent or recurring pain in the lumbar region of the spine to the pelvis ( 8 ) and is the most common reason for individual suffering and utilization of health care services across the lifespan ( 3 ). The experience of pain can be influenced by several factors, including, but not limited to, race, socioeconomic status (SES) and neighborhood-level characteristics, advanced age, and gender ( 9 , 10 ). Mounting evidence suggests disparities and inequities in pain management exist among vulnerable subgroups that are influenced by social determinants of health ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research reported around the world confirms that area-based deprivation indexes are associated with equity in health status and health outcomes measured in terms of morbidity and mortality. Area-based deprivation was found to be associated with higher cancer mortality in Hong Kong, China [25] and with higher levels of anxiety among patients with advanced cancer in the United States [26], while a South Korean study suggested community deprivation levels to influence individual health behaviors [27]. A Northern Ireland study reported a significant correlation of the prescribing of multiple drug classes with socio-economic deprivation levels [28].…”
Section: Discussionmentioning
confidence: 98%